Models for galaxy and massive black hole formation and early evolution. Issue Volume 15:Issue S359(2020) (March 2019) - Weinberger, Rainer
Abstract: Models for massive black holes are a key ingredient for modern cosmological simulations of galaxy formation. The necessity of efficient AGN feedback in these simulations makes it essential to model the formation, growth and evolution of massive black holes, and parameterize these complex processes in a simplified fashion. While the exact formation mechanism is secondary for most galaxy formation purposes, accretion modeling turns out to be crucial. It can be informed by the properties of the high redshift quasars, accreting close to their Eddington limit, by the quasar luminosity function at peak activity and by low-redshift scaling relations. The need for halo-wide feedback implies a feedback-induced reduction of the accretion rate towards low redshift, amplifying the cosmological trend towards lower accretion rates at low redshift.